PERENCANAAN DAN PERANCANGAN GEDUNG CONVENTION CENTRE DIKABUPATEN PENUKAL ABAB LEMATANG ILIR (PALI) - Abdul Yasir; Anta Sastika; Supriyono Supriyono (Jurnal Tekno Global, 2018)
Regency of Penukal Abab Lematang Ilir (PALI) is one of regencies in South Sumatera Province. As newly formed districts cause the lack of facilities and infrastructure to support public needs. This is because the local government is currently more focused on development and infrastructure. As a result of the unavailability of various public facilities in the Pali regency, many activities and events held by local government agencies and private sector should be held in places that are not in accordance with its function, due to the absence of buildings that can accommodate these activities. The development of Pali district into a new district will certainly be a lot of large-scale events to be held in Pali District. The planning of the Convention Center in Pali Regency is planned with the assumption that 10 years ahead the condition of urban infrastructure and economy of Pali regency have progressed, so that there will be more activities in Pali regency, and more and more investors entering Pali regency can become target market for the Convention Center Building.Key words: Public Facilities, events, infrastructure, Convention Center.